ADAPTATION OF SARS_COV-2 MICROSCOPIC IMAGERIES INTO ABSTRACT PAINTING (UNIVERSITY OF JOS FINE AND APPLIED ARTS JOURNAL, 2023)
Corona virus disease (COVID-19) is an infectious disease that has been a global health concern since 2019. It is caused by Severe Acute Respiratory Syndrome Coronavirus 2 (SARS_Cov-2) and the microscopic images of this dreaded virus adorn the screens of many mass media worldwide. These images are a dichotomy of the harmful and deadly nature of the virus. They appear aesthetically fascinating and display interesting patterns; motivating the researchers to carry out this study. This study, therefore, attempts to adapt the images to create painting compositions. Such has been attempted by artists like David Goodsell who composes microscopic data of viruses mostly for scientific advancement. The study adopts the notion of biomimicry. It also adopts the concept of abstract expressionism as derived from the works of Nigerian artist Gani Odutokun. The practice-based research methodology was employed for the study and data was garnered from secondary sources such as the Internet, journals, and magazines. The study concludes that the microscopic world has been explored marginally for artistic innovations and adds that studies such as this can narrow the gap between art and science and result in unique ideas.
Keywords: Corona Virus; SARS_Cov-2; Adaptation; Abstract; Painting